ANALISIS PENGARUH PROMOSI, EMOSI POSITIF DAN STORE ENVIRONMENT TERHADAP PERILAKU IMPULSE BUYING (Studi Kasus Pada Pelanggan Swalayan Tong Hien di Kota Semarang) - Putra, Brian Permana; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2014)
Research drop was triggered by buying kind of unplanned 2006-2011 always year increased every year.The planned purchase always is decreasing every year.Indonesian consumers buy more interested in the kind of unplanned than planned, by purchase so marketers need appropriate strategy to consumers are interested in purchasing kind of unplanned.The purpose of this research is to find out the influence of a promotion positive emotion and store environment against impulse buying on supermarkets tong hien.Population in this research is a self-service tong hien costumer. Respondents engaged in this study about 100 samples.Linear regression analysis used is doubleThe result of multiple regression analysis already done obtained the result that is, y = 0,490 (x1) + 0,239 (x2) + 0,207 (x3).Independent variable most influential against the dependent variable is variable promotion ( 0,490 ) followed by variable positive emotion ( 0,239 ) and last is variable store environment ( 0,207 ).Results test t prove that all variables indenpenden ( promotion, positive emotion, and store environment ) has a positive influence against the dependent variable namely impulse buying.And coefficients of determination ( adjusted rÂ² ) is result of 0,730.It means that 73 % decision purchase affected by variable promotion positive emotion, and store environment.And the rest is 27 % affected by another variable.